Sierra Leone : Investment Climate Policy Note - World Bank (Washington, DC, 2014)
This Investment Climate Policy Note (ICPN) for Sierra Leone evaluates the country's business environment by: (i) analyzing barriers to private sector investment and growth and how they vary among different types of firms; (ii) benchmarking Sierra Leone's investment climate and firm performance to that of other countries; and (iii) providing recommendations to promote and strengthen the private sector. The ICPN is supported by the statistical analysis of a 2009 enterprise survey of 150 formal, manufacturing and service firms with five or more employees based in Western Area/Freetown and Kenema, two of Sierra Leone's major urban centers. The ICPN is organized as follows. Chapter one provides context for Sierra Leone's business environment. Chapter two discusses the performance of Sierra Leone firms, with a focus on labor productivity. Chapter three examines how investment climate constraints cost businesses money and time, discusses main bottlenecks to conducting business as identified by managers of Sierra Leone firms, and reviews obstacles related to electricity supply, tax rates, informality, corruption and access to land. Chapter four analyzes data on how firms access and use finance, and chapter five discusses exports and internationalization in Sierra Leone. Chapter six concludes and provides policy options to improve the investment climate.